2004
DOI: 10.1051/0004-6361:20031489
|View full text |Cite
|
Sign up to set email alerts
|

The effect of signal digitisation in CMB experiments

Abstract: Abstract. Signal digitisation may produce significant effects in balloon -borne or space CMB experiments, when the limited bandwidth for downlink of data requires loss-less data compression. In fact, the data compressibility depends on the quantization step q applied on board by the instrument acquisition chain. In this paper we present a study of the impact of the quantization error in CMB experiments using, as a working case, simulated data from the P/LFI 30 and 100 GHz channels. At TOD level, the effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…This protocol is substantially in accordance with the results reported by Maris et al [5]. The main difference is operative.…”
Section: Virtually Lossless Compressionsupporting
confidence: 92%
See 1 more Smart Citation
“…This protocol is substantially in accordance with the results reported by Maris et al [5]. The main difference is operative.…”
Section: Virtually Lossless Compressionsupporting
confidence: 92%
“…In fact, for an astronomer a scientific frame is not simply a scene to be reproduced with a more or less high fidelity, but a 2D measure of a scalar field representing fluxes. Then, as for any other measure, random and systematic errors must be carefully assessed, quantified, and kept under strict control [5]. A common practice to achieve this goal, given the root mean square (RMS) of the noise introduced by the analog instrument, is that the step size of the uniform threshold quantizer (UTQ) is chosen accordingly, based on application requirements; for example, target detection, and the outcome quantization levels are transmitted without further loss.…”
Section: Introductionmentioning
confidence: 99%
“…The sky and reference load time-ordered data are then "mixed" to reduce variability due to correlated noise and drifts, and requantised to an equivalent 6 σ/q ∼ 9, leading to a σ/q ∼ 2 for the sky and reference recovered signals. This process adds less than 0.05% extra white noise (see Maris et al 2004 for a description of the effects of quantisation on the noise distribution). Finally, the mixed and re-quantised time-ordered data are recoded using an adaptive lossless algorithm into packets of maximum capacity of 980 bytes equivalent to about 1172 compressed samples.…”
Section: On-board Data Acquisition Handling and Transmission To Groundmentioning
confidence: 99%
“…Previous optimisation studies (Maris et al 2004) demonstrated that a quantisation ratio σ/q ∼ 2 is enough to satisfy telemetry requirements without significantly increasing the noise level. This has been verified during calibration tests using the so-called "calibration channel", i.e., a data channel containing about 15 minutes per day of unquantised data from each detector.…”
Section: White Noise Sensitivity and Noise Effective Bandwidthmentioning
confidence: 99%